CONCENTRATION OF Hg, Cd, Cu, Pb AND Zn IN SEDIMENT OF GRESIK WATERS - Lestari Lestari; Fitri Budiyanto (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Gresik coastal waters is one of the areas that have a potential risk for environmental damage due to anthropogenic activities. Water and sediment samples were collected to determin  metals concentration and to identify sediment quality in February 2012. Twelve samples were collected for analysis of mercury (Hg) and four other metals (Cd, Cu, Pb, and Zn). Mercury was analyzed using USEPA method 7471B with Flameless-AAS (Atomic Absorption Spectrophotometer) varian type SpectarAA VGA 20-76 and the other metals were analyzed using USEPA 30050B with Flame-AAS. Results showed that ranges and average concentrations of Hg were 0.04-0.33 (0.13) mg/kg, Cd 0.08-3.05 (0.64) mg/kg, Cu 23.7-234.0 (85.5) mg/kg, Pb 1.74-12.7 (4.29) mg/kg, and Zn 77.0-405.0 (133.0) mg/kg. Metals with high concentrations were detected in some places and by SQG-Q, surface sediment showed a moderate impact level of biological adverse effects in aquatic sediments. Keywords: mercury, heavy metal, sediment, Gresik.